She's my nanny: Discourses and perceptions of children who are cared for by child and adolescent domestic workers - Sarai Miranda (economic sociology. perspectives and conversations, 2023)
The goal of this article is to explore and describe how social inequalities are replicated in the discourse of children who are cared for by child and adolescent domestic workers. The local context analyzed is the Mexican city of San Cristóbal de Las Casas, Chiapas, where child and adolescent domestic work is part of a social dynamic based on the normalization of servitude relations and hierarchical relations between mestizo families and indigenous and migrant families.
Keywords: 300